An mHealth Intervention for Persons with Diabetes Type 2 Based on Acceptance and Commitment Therapy Principles: Examining Treatment Fidelity - Nes, Andréa Aparecida Gonçalves; van Dulmen, Sandra; Brembo, Espen Andreas; Eide, Hilde (JMIR Publications, 2018)
BackgroundWeb-based interventions are becoming an alternative of treatment aimed to support behavioral changes and several advantages over traditional treatments are reported. New ways of delivering an intervention may result in new challenges regarding monitoring of treatment fidelity (TF) which is essential to ensure internal and external validity. Despite the importance of the theme, only a few studies in this field are reported. ObjectiveTo examine TF of a mobile phone delivered intervention based on Acceptance and Commitment Therapy (ACT) with electronic diaries and written situational feedback for persons with diabetes mellitus type 2, the recommendations from the Behavior Change Consortium (BCC) established by The National Institutes of Health (NHI) were applied. To analyze fidelity, they recommend 5 areas to be investigated (1) design of the study, (2) provider training, (3) delivery of treatment, (4) receipt of treatment, and (5) enactment of treatment. In the current study, these areas were examined based on the analysis of therapists' adherence to the treatment protocol and participants' and therapists' experience with the intervention. MethodsTo investigate the therapists' adherence to the treatment protocol, a total of 251 written feedback text messages were divided into text segments. Qualitative thematic analyses were then performed to examine how ACT and other therapeutic processes were used in the feedback by the therapists. For the therapists' and participants' experience analysis, participants answered a self-reported questionnaire and participated in 2 interviews. The therapists continuously reported their experiences to the researcher responsible for the project. ResultsThe results show high adherence to the TF strategies 20/21 (95%) applicable items of the fidelity checklist recommended by NHI BCC were identified in the present study. Measured provider skill acquisition post-training was the only item absent in the fidelity checklist. The results also show high therapists' adherence to the treatment protocol. All ACT processes (values, committed action, acceptance, contact with the present moment, self as context and cognitive defusion) were found in the coded text segments of the feedback in addition to communication and motivation strategies. For 336/730 (46%) of total possible text segments coded independently by 2 researchers, the interrater reliability measured by Cohen's kappa was .85. The evaluation of participants' and therapists' experience with the intervention was generally positive. ConclusionsBased on the analyses of therapists' adherence to the treatment protocol grounded by ACT-principles and participants' and therapists' experience with the intervention, the 5 areas of TF recommended by NHI BCC were analyzed indicating a high level of TF. These results ensure an appropriate level of internal and external validity of the study and reliable intervention results and facilitate a precise replication of this intervention concept. Web-based psychological interventions to support people with chronic conditions are becoming increasingly more common. This study supports the results from a previous study which indicated that ACT could be reliably delivered in a written web-based format. Trial RegistrationClinicalTrials.gov NCT01297049; https://clinicaltrials.gov/ct2/show/NCT01297049 (Archived by WebCite at http://www.webcitation.org/70WC4Cm4T)